2022
DOI: 10.3390/ejihpe13010001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Stress and Teachers Well-Being: The Mediating Role of Sense of Coherence and Resilience

Abstract: The outbreak of the COVID-19 pandemic has impacted many professions with short-, medium-, and long-term consequences. Hence, this study examined the mediating role of sense of coherence (SOC) and resilience in the relation to COVID-19 stress and teachers’ well-being (TWB). It recruited 836 teachers from Ethiopia’s higher-education institutions, of which 630 (75.4%) were men and 206 (24.6%) were women, with a mean age of 32.81 years and a standard deviation of 6.42. Findings showed that COVID-19 stress negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…A recent study reinforces our finding, highlighting the significance of psychological resilience as a predictor of post-traumatic growth when individuals are engaged in disaster preparedness and hence perceive themselves as being more able to cope and experience growth after stressful traumas [44]. Additionally, our study confirms findings from a recent study that emphasized the critical role of social support in shaping teachers' well-being and post-traumatic growth [18]. Resilience and social support in the current study may have helped teachers face the challenges in their work and personal lives and consequently may have reduced their emotional distress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A recent study reinforces our finding, highlighting the significance of psychological resilience as a predictor of post-traumatic growth when individuals are engaged in disaster preparedness and hence perceive themselves as being more able to cope and experience growth after stressful traumas [44]. Additionally, our study confirms findings from a recent study that emphasized the critical role of social support in shaping teachers' well-being and post-traumatic growth [18]. Resilience and social support in the current study may have helped teachers face the challenges in their work and personal lives and consequently may have reduced their emotional distress.…”
Section: Discussionsupporting
confidence: 90%
“…Resilience is a psychological resource that refers to positive adaptation and functioning in the face of a crisis [15,16]. Studies conducted during the COVID-19 pandemic found that teachers' resilience was positively related to their emotional state and functioning [11,17], and that resilience is a significant positive predictor of teacher well-being [18].…”
Section: Introductionmentioning
confidence: 99%
“…Positive TWB levers were often determined based on teachers' effective use of their personal resources and personality traits to overcome stress and augment their well-being as fully functioning professionals when working within a school environment in constant flux and turbulence. Empirical testimony to such positive TWB correlates in the COVID-19 period illustrate the invaluable role of teachers' resilience and utilization of coping strategies, maintaining a clear and organized work schedule and the generation of feelings of professional mastery [128]; teachers' perceived need to (a) adopt proactive physical TWB self-care strategies (e.g., yoga, meditation classes) and (b) regain their professional selfesteem by being recognized for the services they provide in public education in the middle of the pandemic [98]; teacher confidence as manifest in their ability to manage student behaviors [138]; obsessive work passion found to be associated with considerable gains in work engagement, work performance, and affective well-being by eliminating negative emotions and guilt sentiments for any faults and inadequacies and by moderating the effects of excessive workload and organizational constraints [139]; increased levels of intrinsic motivation and positive attitudes toward the teaching profession that impelled teachers to persist in teaching despite the ERT-associated hardships [130]; personal resource readiness to innovate and high levels of self-efficacy with digital media found to be associated with perceived changes in TWB, elevated levels of job satisfaction, and minimum exhaustion for teachers [108]; a perceived sense of coherence at work and resiliency that positively predicted TWB acting as mediators between COVID-19 stress and TWB and as valuable personal resources that enable teachers to flourish in life and nurture their well-being in times of crisis [140]; and the use of positive coping 'problem-focused' (e.g., planning for the future, developing new technological skills) and 'emotion-focused' strategies (e.g., personal skills and capacities, connecting with colleagues, family and friends) [131], which were found to be associated with enhanced TWB, particularly when combined with sound a psychological state and work characteristics [141]. Indeed, in a study by [134], the use of effective coping strategies during the COVID-19 pandemic further revealed that language teachers who tended to opt for active, approach-oriented coping strategies, first by accepting the situation and then by attempting to deal with it using planning, immediate action, and reframing, as well as seeking emotional support, were all predictive of high levels of TWB and health, positive emotions (happiness and growth during trauma), and resilience.…”
Section: B Twb Levers During the Covid-19 Eramentioning
confidence: 99%
“…The instrumentation utilized for TWB measurement in these studies consisted of (a) the adaptation of widely established and standardized psychometric scales of wellbeing and mental health such as the International Barometer of Education Personnel's Health and Wellbeing [142], the World Health Organization Well-being Index [115,134], Ryff's Psychological Well-Being Scales [101,102], the PERMA Profiler Questionnaire [99,140], Diener et al's (2009) Psychological Wellbeing Scale [103,139], the modified BBC Subjective Well-being scale (BBC-SWB) [118], and Positive and Negative Affect Schedule (PANAS) [126] and (b) the compilation of context-specific well-being instruments, valid for experimentation within a particular educational context. Instances of such scales are Alves et al's [105] Well-being and Health Perception Scale and Perception Scale of Well-Being with the Professional Situation in Times of Pandemic, Eadie's [98] Early Childhood Professional Wellbeing scale, Smith and James' [141] Wellbeing Process Questionnaire, and Trindade et al's [106] Questionnaire of the Perception of Well-Being at Work, (c) the use and appropriation of instruments used in prior TWB research in view of COVID-19 new reality, e.g., [112,115,117,145], (d) the development of new survey COVID-19-oriented questionnaires in relation to TWB [107,116,143], and (e) the use of scales that measure TWB indirectly as a function of work-related anxiety [121], depression, general and specific life satisfaction [124,127], teacher stress and exhaustion [100,108], job satisfaction [109,137,138], teacher burnout [137], teacher work engagement, and emotional exhaustion [110,…”
Section: B Twb Levers During the Covid-19 Eramentioning
confidence: 99%
See 1 more Smart Citation